INTEGRATION OF CARE IN HOSPITAL MANAGEMENT: IMPACT ON THE QUALITY AND EFFICIENCY OF HEALTH SERVICES - Narciso de Oliveira, Alexsandro; Helena Brizido Marinho Barreto, Maria; Aparecida de Oliveira Soares, Diely; Marques de Souza, Juliana; Maria Leonel de Bruyn, Ana; Severino Santana, Cléber; Caxico de Abreu Júnior, Fábio; Louise de Bruyn, Anne (Health and Society, 2025)
This study analyzes the impact of care integration in hospital management on the quality and efficiency of health services. Through a systematic literature review of the past five years, 24 relevant studies were selected, addressing different aspects of care integration. The results indicate that care integration is associated with reduced hospital readmission rates, improved patient clinical outcomes, and increased patient satisfaction. Additionally, integration contributes to the operational efficiency of hospitals by reducing wait times for exams and consultations, optimizing the use of hospital resources, and lowering operational costs. Despite the benefits, implementation faces significant challenges such as resistance to change by healthcare professionals and the need for investments in technological infrastructure. Practical recommendations include investing in information and communication technologies, training healthcare professionals, developing integrated protocols, and public policies that encourage care integration. This study highlights the importance of care integration as an effective strategy to improve the quality and efficiency of health services.